Exploring Aspects of Open Educational Resources Through OER-Enabled Pedagogy - Tillinghast, Beth; Fialkowski, Marie K.; Draper, Jennifer (Frontiers in Education, 2020)
In the last decade, much research has taken place that examines various aspects of Open Educational Resources (OER); while, more recently, educators have begun to explore OER-enabled pedagogy. This study uses an explanatory sequential mixed method approach and is unique in that it incorporates the variable of “engagement” with the original “cost,” “outcomes,” “usage,” and “perception” (COUPE) constructs that are often measured in OER research. It is also unique in that it explores OER-enabled pedagogy through the lens of the COUPE framework. This study analyzes the results of the COUPE framework as applied to an undergraduate general education introductory nutrition course at a public university. Course sections involved utilized OER and OER plus open pedagogy. Quantitative and qualitative data were gathered to assess possible differences between the OER and OER plus sections. Conclusions indicate relatively few differences, although the overall response to OER was generally positive across sections, and the OER-enabled pedagogical approach was viewed as positive.